2009
DOI: 10.1590/s1677-55382009000100012
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the presence of functional ß1, ß2 and ß3-adrenoceptors in urothelium and detrusor of human bladder

Abstract: Purpose:We investigated the presence of functional 1, 2 and 3-adrenoceptor in urothelium and detrusor muscle of Materials and Methods: Expression of these adrenoceptors in surgically separated human urothelium and detrusor muscle produced by Results:1, 2 and 3-adrenoceptor in both human urothelium and -adrenoceptors such as procaterol and isoproterenol evoked potent concentration-dependent relaxation of isolated human bladder strips with pD 2 Conclusions:site of actions for the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 19 publications
4
41
0
Order By: Relevance
“…Moreover, solabegron also inhibited field stimulation-induced contraction, which was not mimicked by isoprenaline. In another study with human isolated detrusor strips, solabegron produced relaxation with an EC 50 of 1.9 nM with an efficacy similar to that of isoprenaline (Tyagi et al 2009). Within that study, both solabegron and isoprenaline also inhibited human detrusor tone induced by field stimulation.…”
Section: Isolated Tissue Studiesmentioning
confidence: 89%
“…Moreover, solabegron also inhibited field stimulation-induced contraction, which was not mimicked by isoprenaline. In another study with human isolated detrusor strips, solabegron produced relaxation with an EC 50 of 1.9 nM with an efficacy similar to that of isoprenaline (Tyagi et al 2009). Within that study, both solabegron and isoprenaline also inhibited human detrusor tone induced by field stimulation.…”
Section: Isolated Tissue Studiesmentioning
confidence: 89%
“…It has been shown that urothelial-derived NO can be released in response to mechanical as well as chemical stimulation and may either facilitate or inhibit the activity of bladder afferent nerves conveying bladder sensation (18,42). In this regard, activation of urothelial receptors and release of inhibitory mediators may explain, in part, the mechanism of action for therapies (e.g., ␤ 3 -AR agonists) in treatment of bladder disorders such as the overactive bladder (OAB) (137,283,301).…”
Section: Urothelium-lamina Propria Interactionsmentioning
confidence: 99%
“…Vesicular exocytosis is enhanced by cAMP in various cell types (7,13,19). Metabotropic receptors that regulate cAMP are found in urothelium: G-protein G s -or G i/o -coupled receptors, such as α 2 and β adrenergic (26,27,31) and muscarinic M2 and M4 (8,21,34) receptors. Furthermore, store-operated Ca 2+ entry specifically inhibited adenylyl cyclase type 6 (10,14).…”
Section: Adenylyl Cyclase-camp Pathway Did Not Cause Urothelial Atp Rmentioning
confidence: 99%
“…The adenylyl cyclase-cAMP pathway is upregulated by G s protein. In urinary bladder, β 1 -, β 2 -, and β 3 -adrenoceptors, which are G s -coupled-receptors, are expressed in urothelium (27,31). Among adrenoceptor subtypes in urothelium, α 1D is involved in the induction of ATP release (17), and β activation triggered a production and release of nitric oxide (5).…”
Section: Referencesmentioning
confidence: 99%